Strength Development and Elemental Distribution of Dolomite/Fly Ash Geopolymer Composite under Elevated Temperature - Azimi, Emy Aizat (Materials (Basel), 2020)
A geopolymer has been reckoned as a rising technology with huge potential for application across the globe. Dolomite refers to a material that can be used raw in producing geopolymers. Nevertheless, dolomite has slow strength development due to its low reactivity as a geopolymer. In this study, dolomite/fly ash (DFA) geopolymer composites were produced with dolomite, fly ash, sodium hydroxide, and liquid sodium silicate. A compression test was carried out on DFA geopolymers to determine the strength of the composite, while a synchrotron Micro-Xray Fluorescence (Micro-XRF) test was performed to assess the elemental distribution in the geopolymer composite. The temperature applied in this study generated promising properties of DFA geopolymers, especially in strength, which displayed increments up to 74.48 MPa as the optimum value. Heat seemed to enhance the strength development of DFA geopolymer composites. The elemental distribution analysis revealed exceptional outcomes for the composites, particularly exposure up to 400 °C, which signified the homogeneity of the DFA composites. Temperatures exceeding 400 °C accelerated the strength development, thus increasing the strength of the DFA composites. This appears to be unique because the strength of ordinary Portland Cement (OPC) and other geopolymers composed of other raw materials is typically either maintained or decreases due to increased heat.